A Discursive Construction of the Pragmatic Identities of Chinese College EFL Teachers in Evaluative - Zhuo Chen; Yunlong Qiu (SAGE Open)
Pragmatic identity has received much attention in pragmatic studies. However, few studies have examined teacher’s pragmatic identity construction in the shuoke context. Shuoke is a teaching activity in which a teacher explains the teaching design and process to colleagues or experts for feedbacks. To address this research gap, this study applies Pragmatic Identity Theory to investigate the discursive construction of the pragmatic identities of Chinese college EFL teachers. Data was collected through a representative contest of evaluative shuoke , a type of shuoke used to help teachers assess and improve their teaching ability. It is found that five types of pragmatic identities are constructed, which can be categorized as information deliverer, creator, researcher, value guider and reflector. The discursive practices used for constructing these pragmatic identities include speech acts, grammar, and lexical features. These findings further validate Pragmatic Identity Theory in the shuoke context and provide insights for teachers to practice shuoke effectively from the perspective of pragmatic identity.